1985
DOI: 10.1109/edl.1985.26256
|View full text |Cite
|
Sign up to set email alerts
|

First life-test results on planar p-i-n InGaAs/InP photodiodes passivated with SiO2or SiNx+SiO2or SiNxlayers

Abstract: This ietter reports the results obtained with planar p-i-n photodiodes realized using three different passivating coatings and compares their performances and long-term stability in view of highly reliable component development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

1987
1987
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 4 publications
0
5
0
3
Order By: Relevance
“…Hydrogenated amorphous silicon nitride ͑a-SiN x :H͒ films grown by plasma-enhanced chemical vapor deposition ͑PECVD͒ have received extensive interest 1 not only because of their many useful applications in the microelectronics such as passivation of some capless devices, i.e., GaAs metal-semiconductor field effect transistor amplifier, 2 planar p-i-n InGaAs/InP photodiodes, 3 and metal-insulator semiconductor devices, but also due to their low cost, easy fabrication process, and good masking property. However, these a-SiN x :H films are usually not applicable in low-temperature microelectronic processings because the film properties are poor when deposited at low temperature.…”
mentioning
confidence: 99%
“…Hydrogenated amorphous silicon nitride ͑a-SiN x :H͒ films grown by plasma-enhanced chemical vapor deposition ͑PECVD͒ have received extensive interest 1 not only because of their many useful applications in the microelectronics such as passivation of some capless devices, i.e., GaAs metal-semiconductor field effect transistor amplifier, 2 planar p-i-n InGaAs/InP photodiodes, 3 and metal-insulator semiconductor devices, but also due to their low cost, easy fabrication process, and good masking property. However, these a-SiN x :H films are usually not applicable in low-temperature microelectronic processings because the film properties are poor when deposited at low temperature.…”
mentioning
confidence: 99%
“…lité temporelle des composants [1]. D'autres facteurs peuvent donc jouer un rôle important, tels que la ' préparation de la surface avant le dépôt, ou la présence d'oxyde natif [5], et sa composition [7].…”
Section: Gainasunclassified
“…Pour optimiser la sensibilité de ces dispositifs, il est nécessaire de minimiser le courant d'obscurité et d'assurer la stabilité des caractéristiques en fonctionnement. Actuellement, il apparaît que le courant d'obscurité reste souvent dominé par un courant de surface que seule une passivation efficace permet de réduire et de stabiliser [1,2].…”
unclassified
“…Furthermore, the electrical behavior of the silicon nitride/silicon interface is not as well understood as the silicon dioxide/silicon interface even though the electrical characteristics of the insulator/semiconductor interface is known to play an important role in determining the reliability of the devices. 16 In this article careful and detailed capacitance-voltage (C -V) measurements including interface characterization have been undertaken in the MIS configuration for siliconrich, nearly stoichiometric and nitrogen-rich silicon nitride films prepared by plasma enhanced chemical vapor deposition ͑PECVD͒ from silane (SiH 4 ) and ammonia (NH 3 ) with nitrogen dilution. In the present study, we have observed that both electron and hole traps are much lower in concentration for the nitrogen-rich films deposited with nitrogen dilution.…”
Section: Introductionmentioning
confidence: 99%